General banking activities of Uttara Bank Limited : a study on Kalabagan Branch - Saadmani, Fatema Rahman (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.